2021
DOI: 10.1302/0301-620x.103b12.bjj-2021-0447.r1
|View full text |Cite
|
Sign up to set email alerts
|

Wound photography for evaluation of surgical site infection and wound healing after lower limb trauma

Abstract: Aims Deep surgical site infection (SSI) is common after lower limb fracture. We compared the diagnosis of deep SSI using alternative methods of data collection and examined the agreement of clinical photography and in-person clinical assessment by the Centers for Disease Control and Prevention (CDC) criteria after lower limb fracture surgery. Methods Data from two large, UK-based multicentre randomized controlled major trauma trials investigating SSI and wound healing after surgical repair of open lower limb f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These criteria were absence of exudate at gauze; formation of scab covering the wound; the wound must be kept uncovered; no signs of infection or inflammation at nail folds; no signs of erythema or hypergranulation tissue Reyzelman (2000) [26] Healing time was defined as the interval between the day the phenol matrixectomy was performed and the resolution of drainage and inflammatory changes surrounding the nail border. In every case, healing was identified by the principal investigator of the trial Tatlican (2009) [27] Complete healing was defined as the complete reepithelialization of the nail bed and the cessation of drainage Van der Ham (1990) [28] No definition provided Varma (1983) The average time to become pain-free was 3.6 days, with no statistical difference between the groups studied Andre (2018) [33] A and applied to nail surgery [54][55][56]. Despite the clear interest in post operative infection as an outcome, only one trial explored the use of oral antibiotics and found no evidence that they reduced the rate of post operative infection.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria were absence of exudate at gauze; formation of scab covering the wound; the wound must be kept uncovered; no signs of infection or inflammation at nail folds; no signs of erythema or hypergranulation tissue Reyzelman (2000) [26] Healing time was defined as the interval between the day the phenol matrixectomy was performed and the resolution of drainage and inflammatory changes surrounding the nail border. In every case, healing was identified by the principal investigator of the trial Tatlican (2009) [27] Complete healing was defined as the complete reepithelialization of the nail bed and the cessation of drainage Van der Ham (1990) [28] No definition provided Varma (1983) The average time to become pain-free was 3.6 days, with no statistical difference between the groups studied Andre (2018) [33] A and applied to nail surgery [54][55][56]. Despite the clear interest in post operative infection as an outcome, only one trial explored the use of oral antibiotics and found no evidence that they reduced the rate of post operative infection.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments were undertaken by a trained healthcare professional within the research team rather than by an independent clinician or dermatologist. We have previous experience of judging adverse skin outcomes, including redness, spreading erythema, exudate and wound healing, in other patient populations, where inter-rater reliability was found to be substantial 33 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] The reasons may be: that spinal and joint surgical incisions are cleaner, and most trauma surgeries are type III incisions, with an extensive range of surgical invasion, resulting in more soft tissue damage, thereby increasing the incidence of SSI. [ 15 ] Orthopedic “trauma” surgery patients become a population with nosocomial infections because of the relative length of orthopedic surgery, the widespread use of orthopedic implants, and the many invasive factors. [ 6 ] The higher infection rate of the surgical site in arthroplasty may be related to the more incredible surgical trauma, and postoperative local blood supply is affected to a certain extent and is not conducive to postoperative healing and other reasons.…”
Section: Discussionmentioning
confidence: 99%